Effect of nitrogen limitation on polyhydroxyalkanoates production efficiency, properties and microbial dynamics using a soil-derived mixed continuous culture. Issue 1 (2nd January 2019) - Ntaikou, Ioanna; Koumelis, Ioannis; Kamilari, Maria; Iatridi, Zacharoula; Tsitsilianis, Constantinos; Lyberatos, Gerasimos
ABSTRACT: In the present study, a soil-derived mixed microbial consortium was developed for polyhydroxyalkanoates (PHAs) production via nutrient limitation. The enhanced consortium was then cultured continuously in sequential batch and the effect of different nitrogen to carbon ratios (N:C) on the yields and properties of produced PHAs and on the changes of the microbial population were investigated. In all cases, the produced polymers were identified as blends or co-polymers of 3-hydroxybutyrate (3HB) and 3-hydroxyvalerate (3HV) units, with 3HB being the dominant monomer. The degradation profile and the transition temperatures of the produced PHAs were further assessed and compared, as well as the molecular weights which ranged from 77.10 4 Da to 180.10 4 Da. In order to further investigate the effect of culturing conditions on the development and alteration of the microbial consortium, the Nile blue live staining was applied in the mixed cultures at the end of each operational period. Various fluorescent single colonies were selected based on differences in their morphology and were identified. Finally, the alterations in microbial diversity and community composition assessed via the RISA profiling method (rRNA Intergenic Spacer Analyses), resulted in the identification of a number of dominant organisms.